Bipolar and MOS analog integrated circuit design - Grebene, Alan B., 1939- (Wiley-Interscience, 2003)
A practical, engineering book discussing the most modern and general techniques for designing analog integrated circuits which are not digital (excluding computer circuits). Covers the basics of the devices, manufacturing technology, design procedures, shortcuts, and analytic techniques. Includes examples and illustrations of the best current practice.